Helium Inhalation Suicide: Hypoxic Asphyxia and Gas Embolism as Dual Mechanisms of Death: A Case Report - Dear Prof.Ivan Tsranchev; Gudelova, Teodora; Gudelova, Teodora; Hadzhieva, Kristina; Dineva, Plamena; Sotirova, Mirena; Hristeva, Kaloyana; Ezeldin, Fares; Dimitrov, Dimitar; Fasova, Antoaneta; et al. (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Helium is an inert gas without inherent toxic properties, which explains its widespread use in both industrial and medical settings. However, despite its chemical inertness, inhalation of helium can cause severe oxygen displacement within the respiratory system, leading to tissue hypoxia and potentially fatal outcomes. Case Presentation: Cases of helium intoxication pose particular clinical and forensic difficulties because toxicological examinations may not always produce positive findings. Death associated with helium exposure is primarily caused by hypoxia resulting from the mechanical replacement of oxygen during breathing. Conclusion: Due to the largely non-specific morphological findings observed at autopsy, establishing the cause and manner of death requires a multidisciplinary approach that integrates scene investigation, forensic pathology, toxicology, and criminalistic analysis.